Avrupa Sanat Müziği Bağlamında Eleştiri - Özkan, Hediye Dilek (Sosyal Bilimler Enstitüsü, 2007)
Müzikte eleştiri; beste, besteci, icra, yayın ve sunum konularının, gözlemler ve farklı yaklaşımlar ile bilgi ve deneyime dayalı bir şekilde ele alınarak, sözlü ve/veya yazılı olarak değerlendirilmesi ve yorumlanmasıdır. Müziksel eleştiri yazıları; Avrupa'da 18. yüzyılın sonunda çeşitli müzikal yayınlarda basılmıştır, 19. yüzyılda ise Almanya, İngiltere, İtalya ve Fransa'nın gazetecilik anlayışı çerçevesinde profesyonel bir platformda, Avrupa Sanat Müziği'ni geliştirmeye yönelik olarak varlığını sürdürmüştür. 20. yüzyılda bilim ve sanattaki akımlar tüm dünyada görülmeye başlanmıştı. Bu değişiklikler müzik eleştirisini; var olan müzikal akımların çerçevesinde, akademik temellere dayalı ve bilimsel olarak süreli yayınlar ve gazetelerde yer alması ve yöntemlerdeki ayırımlar açısından da etkiledi. Bu çalışma; Avrupa Sanat Müziği bağlamında eleştirinin tanımı, sanat eleştirisi, müzik eleştirisi, müzik eleştirisi ve estetik, müzik eleştirisinin tarihsel gelişimi, bir eleştirmenin nitelikleri, Türkiye'de müzik eleştirisi konularını kapsamaktadır. Bu bağlamda; bu çalışma Avrupa ve Türk müzik eleştirmenleri ve yayınlarından bahsetmektedir ve Avrupa Sanat Müziği tarihini kronolojik olarak açıklamaktadır.

Music criticism means evaluating and interpreting, orally and/or in written form, musical compositions and their composers, performers, broadcasting and presentations through observation and different approaches based on knowledge and experience. Music critiques, which began with various musical journals published in Europe in the late 18th century, continued its existence on a professional platform throughout the 19th century with the help of the musical journals prepared in Germany, England, Italy and France for the purpose of improving music in Europe. In the 20th century, various currents in science and art started to emerge across the world. These changes also had an effect on music criticism, diversifying the methods of criticism, and caused music criticism in journals and periodicals to be performed scientifically also in line with the existing musical currents and on an academic basis. This study contains that issues are definition of criticism, art criticism, music criticism and esthetics, historical development of music criticism, approaches of criticism, and the qualities of a critic, music criticism in Turkey. Within that context, this study explains the chronological history of European art music criticism and also mentions Turkish and European music critics and publications.
Criticism In The Context Of European Art Music
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2007
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Social Sciences, 2007
Keywords: Müzik; Avrupa; Avrupa sanatı; Eleştiri; Müzik; Müzik eserleri; Sanat eleştirisi; Sanat müziği; Music; European; European art; Criticism; Music; Music works; Art criticism; Art music